Awake : a memoir - Hatmaker, Jen (Avid Reader Press, 2025)
From Jen Hatmaker beloved New York Times bestselling author and host of the "For the Love podcast" -- comes a brutally honest, funny, and revealing memoir about the traumatic end of her twenty-six-year-long marriage, and the beginning of a different kind of love story.